Alternative 3' splice acceptor sites modulate enzymic activity in derivative alleles of the maize bronze1-mutable 13 allele. - Okagaki, R J (1992)
The defective Suppressor-mutator (dSpm)-induced allele bronze1-mutable 13 (bz1-m13) and many of its derivative alleles are leaky mutants with measurable levels of flavonol O3-glucosyltransferase activity. This activity results from splicing at acceptor site-1, one of two cryptic 3' splice sites within the dSpm insertion in bz1-m13. In this study, splicing in bz1-m13 change-in-state (CS) alleles CS-3 and CS-64 was shown to be altered from bz1-m13; previous work found altered splicing in CS-9. CS-64 is a null allele and lacks the acceptor site-1-spliced transcript because this site is deleted. CS-3 and CS-9 had increased levels of the acceptor site-1 transcript relative to bz1-m13 and increased enzymic activities. A deletion in CS-9 altered splicing by eliminating acceptor site-2. Both acceptor sites were intact in CS-3, but a deletion removed most of a 275-bp GC-rich sequence in dSpm. This suggests that GC-rich sequences affect splicing and is consistent with models postulating a role for AU content in the splicing of plant introns. Splicing does not necessarily occur, however, at the junction of AU-rich intron sequences and GC-rich exon sequences.